(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted in medium highland at Dacope, Khulna during rabi season of 2010-11. The aim of the study was to observe the effect of integrated use of bio-slurry along with inorganic fertilizer on the performance of water melon grown in AEZ 13. The experiment was laid out in a randomized complete block design with four replications. Three fertilizer doses viz. T1 : Soil test based inorganic fertilizer dose for high yield goal (HYG), T2 : Cowdung bio-slurry @ 5t/ha + IPNS basis inorganic fertilizer dose for high yield goal and T3 : Farmers practice (average of 20 farmers surveyed) were taken as treatment. Results showed that yield and yield contributing characters of water melon were significantly influenced by the treatments. The highest fruit yield (44.50 t/ha) was recorded in cowdung bio-slurry@ 5 t/ha + IPNS basis inorganic fertilizer dose (T2) followed by T1 (40.27 t/ha). The lowest yield (35.20 t/ha) was obtained from farmers practice. Economic analysis also revealed that the gross return (Tk. 534000.00/ha) and gross margin (Tk. 427515.00/ha) were higher in T2. Benefit-cost ratio (BCR) was also higher in T2 (5.01). DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22097 J. Environ. Sci. & Natural Resources, 6(2): 61-63 2013